(2x+2)(2x-2)=60

Simple and best practice solution for (2x+2)(2x-2)=60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+2)(2x-2)=60 equation:



(2x+2)(2x-2)=60
We move all terms to the left:
(2x+2)(2x-2)-(60)=0
We use the square of the difference formula
4x^2-4-60=0
We add all the numbers together, and all the variables
4x^2-64=0
a = 4; b = 0; c = -64;
Δ = b2-4ac
Δ = 02-4·4·(-64)
Δ = 1024
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1024}=32$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-32}{2*4}=\frac{-32}{8} =-4 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+32}{2*4}=\frac{32}{8} =4 $

See similar equations:

| 6y+9=6y-6 | | (8h–2)–(5-3h)= | | y-5/6=10 | | 3y=36/y | | (3^2x)-(3^x+4)=810 | | 5*4g=3(g)+170 | | 4x+6=9x+70 | | 3^2x-3^x+4=810 | | X+10((x+2)^.5)-22=0 | | 4y2-5y+2=6y2-5 | | 5÷x+1=4÷3 | | 7x–14=5x+12 | | (5÷x)+1=4÷3 | | (3)/(x-4)=1 | | 4p/3=12/1 | | (5÷x)+1=(4÷3) | | 15428x-16=-16 | | d+1/3=4 | | 8x+17+6x-7+3x-29=180 | | 2x+8=6+6x | | 24=2n+10 | | 4a-2=19 | | 80=16*v | | X³+y³=8 | | √9/64x=4 | | X3+y3=8 | | 2+(x+4)=(2+x)+4 | | n÷8-4=-7 | | 2x+3+3x-1=52 | | -3(-2b-1)=21 | | (5/4)x+7=13+x | | 2m-44=76-8mm= |

Equations solver categories